Bond strength of hard chairside reline resins to a rapid polymerizing denture base resin before and after thermal cycling - Neppelenbroek, Karin Hermana [UNESP]; Pavarina, Ana Claudia [UNESP]; Gomes, Mauricio Neves [UNESP]; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP] (FapUNIFESP (SciELO), 2006)
Purpose: This study assessed the shear bond strength of 4 hard chairside reline resins (Kooliner, Tokuso Rebase Fast, Duraliner II, Ufi Gel Hard) to a rapid polymerizing denture base resin (QC-20) processed using 2 polymerization cycles (A or B), before and after thermal cycling. Materials and Methods: Cylinders (3.5 mm x 5.0 mm) of the reline resins were bonded to cylinders of QC-20 polymerized using cycle A (boiling water-20 minutes) or B (boiling water; remove heat-20 minutes; boiling water-20 minutes). For each reline resin/polymerization cycle combination, 10 specimens (groups CAt e CBt) were thermally cycled (5 and 55°C; dwell time 30 seconds; 2,000 cycles); the other 10 were tested without thermal cycling (groups CAwt ad CBwt). Shear bond tests (0.5 mm/min) were performed on the specimens and the failure mode was assessed. Data were analyzed by 3-way ANOVA and Newman-Keuls post-hoc test (α=.05). Results: QC-20 resin demonstrated the lowest bond strengths among the reline materials (P<.05) and mainly failed cohesively. Overall, the bond strength of the hard chairside reline resins were similar (10.09±1.40 to 15.17±1.73 MPa) and most of the failures were adhesive/cohesive (mixed mode). However, Ufi Gel Hard bonded to QC-20 polymerized using cycle A and not thermally cycled showed the highest bond strength (P<.001). When Tokuso Rebase Fast and Duraliner II were bonded to QC-20 resin polymerized using cycle A, the bond strength was increased (P=.043) after thermal cycling. Conclusions: QC-20 displayed the lowest bond strength values in all groups. In general, the bond strengths of the hard chairside reline resins were comparable and not affected by polymerization cycle of QC-20 resin and thermal cycling.
Keywords: Acrylic resins; Denture liners; Shear strength